Mistakes were made - Score, Lucy (Score, Lucy. Story Lake series ;, 2026)
He's looking for the perfect wife. She's looking for the perfect one-night stand. Literary agent Zoey Moody doesn't like small town life, but here she is: exiled from Manhattan's publishing scene and trapped in a tiny Pennsylvania town with her BFF and only remaining client, Hazel. The problem? She's totally broke. All she needs is for Hazel's next romance novel to become a gigantic hit, and Zoey will be back in New York. Nothing will stand in her way. Nothing except her six-foot-two-inch landlord, Gage Bishop. He's smart, serious, and sexy. Worst of all, he's ready to settle down. Zoey might be the most beautiful woman Gage has ever met, but it's clear they're all wrong for each other. She's allergic to commitment and can't work a calendar app; he's looking for a wife and has the next five years all planned out. She's afraid of animals. He lives in a literal barn. But when Gage's world is rocked by a devastating family secret, he turns to Zoey for one night to forget everything. That one night just might change everything ... or ruin it. --